Standardization of Electric Vehicle Battery Production in International Electric Bus Transportation Based on the Innovative Modular Principle - Porfirenko, Volodymyr (Standards-related Regional Innovation and International Cooperation, 2025)
This study provides a comprehensive analysis of the development, industrial production, and operational deployment of electric buses in international transportation, with particular attention to the standardization of electric vehicle (EV) battery technologies through a modular rapid-replacement principle. The ongoing transition from internal combustion engine vehicles to electrified transport systems reflects both the global decarbonization agenda and the demand for sustainable long-distance passenger mobility. Electric buses demonstrate clear advantages, including substantial reductions in greenhouse gas emissions, mitigation of urban noise pollution, and higher energy efficiency, thus contributing to the achievement of international climate goals and the modernization of cross-border transport networks. Nevertheless, several technological and infrastructural barriers continue to constrain large-scale adoption. High manufacturing costs of traction batteries, limitations in vehicle driving range, and insufficient charging infrastructure significantly affect operational reliability in long-distance and cross-border contexts. Within this framework, the study evaluates the innovative concept of modular battery replacement, which is designed to standardize battery dimensions and interfaces across manufacturers and enable rapid exchange of depleted modules. Empirical assessments demonstrate that such a system can reduce downtime to 10–15 minutes, enhance operational efficiency, and lower the total cost of ownership relative to conventional diesel bus fleets. The findings confirm that modular battery replacement and standardization constitute a viable technological pathway toward accelerating the adoption of electric buses in international transportation. By ensuring interoperability, minimizing infrastructure dependence, and improving cost-effectiveness, modular systems can play a pivotal role in shaping the future of sustainable, environmentally responsible, and economically efficient passenger mobility.